2018
DOI: 10.1103/physrevmaterials.2.053608
|View full text |Cite|
|
Sign up to set email alerts
|

Thermodynamics, kinetics, and mechanics of cesium sorption in cement paste: A multiscale assessment

Abstract: Cesium-137 is a common radioactive byproduct found in nuclear spent fuel. Given its 30 year half life, its interactions with potential storage materials-such as cement paste-is of crucial importance. In this paper, simulations are used to establish the interaction of calcium silicate hydrates (C-S-H)-the main binding phase of cement paste-with Cs at the nano-and mesoscale. Different C-S-H compositions are explored, including a range of Ca/Si ratios from 1.0 to 2.0. These calculations are based on a set of 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The rich and complex chemistry of silicate species motivates the study of the dissolution and polymerization of silica [12][13][14]. The role of ions, such as alkali, has long being studied [15] because it varies according to the type of material (glass, hydrated glass, gel, zeolite, mineral) and on the chemical environment [16][17][18]. In recent decades, silicates glasses or aluminosilicates binders have been widely studied in the construction industry and other specific areas.…”
Section: Introductionmentioning
confidence: 99%
“…The rich and complex chemistry of silicate species motivates the study of the dissolution and polymerization of silica [12][13][14]. The role of ions, such as alkali, has long being studied [15] because it varies according to the type of material (glass, hydrated glass, gel, zeolite, mineral) and on the chemical environment [16][17][18]. In recent decades, silicates glasses or aluminosilicates binders have been widely studied in the construction industry and other specific areas.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the disordered structure of C-S-H provides multiple acceptor sites for hydrogen bonds, and therefore is significantly more hydrophilic compared to cationic clays that are often used for comparison. Abdolhosseini Qomi and co-workers 8 constructed bulk C-S-H models that correspond to a wide range of compositions that could be used successfully to study both the mechanical and the sorption properties of C-S-H. 11,12 A number of computational studies describe the behavior of beryllium in aqueous solutions on the molecular level. Beryllium preferentially coordinates ligands in tetrahedral geometry, has strong hydrolyzing and polarizing abilities, and shows complex pH-dependent solution chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium silicate hydrate (C-S-H) is the most significant cement hydrate phase that interacts with Cs, and these interactions have been investigated extensively (Missan et al 2018;Haga et al 2019). These interactions have also been studied using atomistic models that considered molecular dynamics or quantum chemistry (Arayro et al 2018;Jian et al 2017;Duque-Redondo et al 2018;Tachikawa et al 2020). The contribution of aggregates in concrete has also been considered (Idemitsu et al 1992;Fuller et al 2014).…”
Section: Introductionmentioning
confidence: 99%